Pengaruh Struktur Modal, Profitabilitas, Ukuran Perusahaan dan Pertumbuhan Perusahaan terhadap Nilai Perusahaan - Rosa, Eifrel; Hermanto, Hermanto (Jurnal Ilmiah Global Education, 2024)
This research aims to explain the relationship between capital structure, profitability, company size and company growth and company value. This research utilizes data that has been adjusted to research criteria sourced from financial reports for the food and beverage industry for the 2018-2022 period. Data collection used a purposive sampling method with exploratory steps, where this research utilized 90 samples from a total of 18 companies over a 5 years period, using the Eviews10 statistical application. The results of this research reveal that capital structure has a positive relationship with company value, profitability is positively correlated with company value, company size is not correlated with company value and company growth has no evidence of having an influence on company value.